(untitled) (Law, State and Telecommunications Review, 2024)
[Purpose] This study delves into the sociology of law to scrutinize instances of fake news and discriminatory insults within information and electronic transaction laws. [Methodology] Utilizing a qualitative content analysis approach, the research relies on video content observations as secondary data to unearth insights. The study uncovers potential hate speech cases dealt with by the West Kalimantan Regional Police, drawing from video content and social media discussions related to EIT Law and circular letters from the Chief of Police. [Findings] The findings highlight various forms of hate speech, encompassing insults, defamation, unpleasant acts, provocation, incitement, and the dissemination of false news. These manifestations occur both in public spaces and through social media channels, providing a comprehensive understanding of the issue. [Practical Implication] This research sheds light on the complexity of hate speech cases and the challenges law enforcement faces, contributing to a more informed approach to handling similar situations. It underscores the need for effective strategies and policies to address these issues within the legal framework. [Originality] This study offers a unique perspective on legal sociology by exploring hate speech within the context of information and electronic transaction laws. It contributes valuable insights that can inform legal practices, policies, and further research in this domain.